Actual influence cost estimation of water resources in coal mining and utilization in China - Li, S. (2020)
This paper summarizes and analyzes the influences of coal mining and utilization on water resources. Quantitative indicators are used to quantify relevant influences and transform the influences from material amount to monetary amount to gain the summation of the influences in the entire process. Results show that mining of coal per ton generally causes depletion of 1.32 m3 water resources, pollution to 0.88 m3 water resources, and destruction of 0.17 m2 water ecological environment on the average, thereby making a comprehensive cost of approximately 50.61 yuan. Taking thermal power industry as an example, per-ton-coal utilization means depletion of water resources of 26.35 m3 and the comprehensive cost of 86.61 yuan. To utilize coal resources scientifically and to respond to the objective requirements of protecting water resource environment, establishing a region/category-based environmental taxation system is proposed to guide the coal industry in developing a highly water-saving but less-water-pollution method.